2021
DOI: 10.1111/ijcp.14186
|View full text |Cite
|
Sign up to set email alerts
|

Family physicians’ awareness and general knowledge of hidradenitis suppurativa: A survey research

Abstract: Rationale, aims, and objective: Medical consultations of family physicians play a key role in early diagnosis and proper management of hidradenitis suppurativa (HS). This study aimed to investigate family physicians' disease awareness, general attitudes, and knowledge of HS. Material-Methods:This cross-sectional descriptive study was conducted with 211 family physicians and residents through a web-based survey. The questionnaire consisted of 25 questions about the demographic characteristics of the participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…7 Only 23.7% of Turkish family doctors felt capable of diagnosing HS, while 21% of them had not received relevant medical training and 63% believed HS to be an infectious disease of the apocrine glands. 8 As our study shows, even dermatologists have difficulty diagnosing HS. 9 Almost 50% of asked dermatologists i Mean ± standard deviation (95% confidence interval).…”
Section: R E S E a R C H L E T T E R Diagnostic Delay In Hidradenitis...mentioning
confidence: 75%
See 1 more Smart Citation
“…7 Only 23.7% of Turkish family doctors felt capable of diagnosing HS, while 21% of them had not received relevant medical training and 63% believed HS to be an infectious disease of the apocrine glands. 8 As our study shows, even dermatologists have difficulty diagnosing HS. 9 Almost 50% of asked dermatologists i Mean ± standard deviation (95% confidence interval).…”
Section: R E S E a R C H L E T T E R Diagnostic Delay In Hidradenitis...mentioning
confidence: 75%
“…A total quantity of 57.4% of family doctors would happily participate in postgraduate courses on HS. 8 Increasing HS publications in non-dermatology journals is important. Only 6.7% of all articles on HS from 2000 to 2020 were published in non-dermatology journals.…”
Section: R E S E a R C H L E T T E R Diagnostic Delay In Hidradenitis...mentioning
confidence: 99%
“… 12 Among family physicians, a recent survey in Turkey demonstrated that while more than 90% were aware of HS as a diagnostic consideration, only 23.7% felt comfortable diagnosing HS in their clinical practices. 13 These studies suggest that there is a need for research on the learning needs of medical students and primary care providers in Canada with respect to diagnosing and managing HS, in order to optimize their training in this area.…”
Section: Discussionmentioning
confidence: 99%
“…8 Family physicians report low confidence in diagnosing and treating the disease, even though at least 80% received some form of HS education during their medical training. 1,9 Patients with a confirmed HS diagnosis are often referred to multiple healthcare providers 10 who typically focus on treating the physical characteristics of the disease, even though HS patients also have higher rates of mental health concerns like depression, anxiety, and suicide. 11 The severity of HS is traditionally classified by Hurley stages I, II, or III, depending on the progression of the disease throughout the body.…”
Section: Hs Diagnosis and Carementioning
confidence: 99%